The Myth of Hylas in Hellenistic Poetry - Kudulytė-Kairienė, Audronė (Literatūra, 2012)
The article deals with the myth of Hylas in hellenistic poetry. According to the myth, Hylas was a young companion of Heracles. When Heracles joined the expedition of the argonauts, he took Hylas into the ship. On the coast of Mysia, Hylas went out to fetch water for Heracles, but was kidnapped by nymphs of the spring and vanished without a trace. The story Hylas’seduction of was popular from at least hellenistic times until late antiquity. The poet Nicander (II cent. B. C.) in his lost work Heteroioumena made this myth aetiological, explaining how the nymphs abducted Hylas and turned him into the echo. The most famous description of this myth was made by Theocritus, Idyll XIII. Apparently, the story of argonauts and Hylas was treated by Callimachus in his lost poem Aetia. It was treated, at great length and with many details and digressions, in the first book of Argonautica (I. 1187–1357). This episode is regarded as one of the most important scenes of Apollonius Rhodius’ poem. It is abundantly clear that there is a close relantionship between Theocritus’ Idyll XIII and the Hylas’ episode in Argonautica. The problem concerning the priority the Hylas-treatments of Apollonius and Theocritus is discussed in narrative, stylistical, linquistic aspects, and a conclusion is made that it was Theocritus who wrote about Hylas first.